46th AIAA Aerospace Sciences Meeting and Exhibit 2008
DOI: 10.2514/6.2008-146
|View full text |Cite
|
Sign up to set email alerts
|

Green Freighter Systems

Abstract: This paper presents the systems architecture of the Green Freighter, a new pilotless freighter aircraft. As no passengers or pilots will fly aboard this freighter aircraft, it is expected that many systems, particularly the environmental control system, could be modified or removed completely. Thus, the options for the new systems architecture will be elaborated on, followed by a description of the environmental control system model. Then the design of the new environmental, temperature and pressure control sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is very suitable for passenger transport because the multibubble offers more usable space, while for cargo transport the option of an aerodynamic shell with pressurized cargo containers seems to be very interesting [4]. For this paper, only the BWB for passenger transport is considered.…”
Section: B Multibubble Blended Wing Body As a Passenger Aircraftmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very suitable for passenger transport because the multibubble offers more usable space, while for cargo transport the option of an aerodynamic shell with pressurized cargo containers seems to be very interesting [4]. For this paper, only the BWB for passenger transport is considered.…”
Section: B Multibubble Blended Wing Body As a Passenger Aircraftmentioning
confidence: 99%
“…This has led to new solutions and considerations. The research that is used as an inspiration for the work in this paper can be found in [1,2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum specific power limits for the motor and power converter were chosen based on NASA 15-year goals. 9,26 Since PMAD was also modeled as a power converter, its technology level was set equal to that of power converter. Since it was expected that the battery would turn out to be the heaviest component among the PG&D subsystems, the maximum limit of battery specific energy was set to a rather aggressive value in order to study its effect on range.…”
Section: A Sensitivity Analysis At Subsystem Vehicle and Mission Levelsmentioning
confidence: 99%